Factors Associated with the Duration of Breastfeeding in the Freiburg Birth Collective, Germany (FreiStill) - Rasenack, R.; Schneider, C.; Jahnz, E.; Schulte-Mönting, J.; Prömpeler, H.; Kunze, M. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: The health benefits of breastfeeding for both infants and mothers are well-documented. The aim of this study was to clarify factors associated with successful breastfeeding. Methods: We performed a prospective, multi-centre cohort study of 443 mothers in person using a standardised questionnaire on postpartum day 1. Women who had started to breast-feed were interviewed by telephone after 3, 6 and 12 months. A statistical analysis was performed using the SAS system. Results: 92 % of women (409/443) were initially breastfeeding. After three months the rate decreased to 74 %, after six months to 61 % and after 12 months to 28 %, respectively. Bivariate analysis revealed a significant positive association with the following factors: maternal age > 35 years, higher educational level, intention to breastfeed on postpartum day one, high motivation after three months, partnerʼs support of the decision to breastfeed, satisfaction with the care provided in the maternity clinic, a positive breastfeeding experience and follow-up care by a midwife. Elective caesarean delivery, the use of breastfeeding aids, formula supplementation early on and the motherʼs concern about the amount of milk correlated negatively. Following a multivariate logistic regression analysis, four factors were correlated with having a positive influence on duration of breastfeeding: higher educational level, satisfaction with the care provided within the maternity clinic, follow-up care by a midwife, and a positive current experience of breastfeeding. Conclusion: Our data demonstrate certain factors successfully influence breastfeeding. Competent care in the maternity clinic, postpartum care by a midwife and a positive experience with breastfeeding increase the rate of breastfeeding and thus have a positive impact on the health of mother and newborn.
Keywords: breastfeeding; maternity hospitals; infant nutrition; baby-friendly hospital; lactation